EFEITO DE PONTAS DE PULVERIZAÇÃO NA DESSECAÇÃO COM DIFERENTES HERBICIDAS ASSOCIADOS À ADJUVANTES. - PESSÔA, Guilherme Martins; COSTA, Brenda Fernandes; BARBOSA, Danilo Ferreira Ramires; ESPÍRITO SANTO, Tiago Lima; SANTOS, Stephany; MENDONÇA, Cristiane Gonçalves (ANAIS DO ENIC, 2020)
-